2017
DOI: 10.1159/000480528
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Inhibits Cell Migration and Invasion in Human Osteosarcoma Cells

Abstract: Background/Aims: Osteosarcoma is a malignant tumor associated with high mortality; however, no effective therapies for the disease have been developed. Several studies have focused on elucidating the pathogenesis of osteosarcoma and have aimed to develop novel therapies for the disease. Quercetin is a vital dietary flavonoid that has been shown to have a variety of anticancer effects, as it induces cell cycle arrest, apoptosis, and differentiation and is involved in cell adhesion, metastasis and angiogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 69 publications
(63 reference statements)
0
44
0
Order By: Relevance
“…Accumulating evidence has shown that natural or dietary agents may be novel therapies for cancer [35,38]. Here, our present study highlights the anti-tumor effects of a natural product, allicin, which mainly involves the suppression of SHP-1-mediated STAT3 signaling.…”
Section: Discussionmentioning
confidence: 60%
“…Accumulating evidence has shown that natural or dietary agents may be novel therapies for cancer [35,38]. Here, our present study highlights the anti-tumor effects of a natural product, allicin, which mainly involves the suppression of SHP-1-mediated STAT3 signaling.…”
Section: Discussionmentioning
confidence: 60%
“…Current stuies support that osteolysis inhibitors might be another treatment to decrease tumour burden [118-120]. Bisphosphonates is a famous bone-targeted agents inhibiting osteoclast activity and decreasing tumour burden [121].…”
Section: Therapeutic and Molecular Interventionsmentioning
confidence: 99%
“…Several therapy, such as osteroprotegerin, RANK-Fc, PTHrp antibodies, and Vitamin-D analogues, are under phase I to III studies. Other target therapy, such as anti-MMP-9,anti-IGF-1R, Quercetin, Osthole and activating aromatic hydrocarbon receptor, were reported in rescent [120, 122-126]. Current treatments mainly target the RANK-RANKL pathway and PTHrP signaling.…”
Section: Therapeutic and Molecular Interventionsmentioning
confidence: 99%
“…The basement membrane and extracellular matrix are protective barriers for cancer cells to metastasize . MMPs, the family of metal matrix enzymes function to digest collagen, which makes cancer cells move to other sites, and are often found upregulated during cancer progression . MMP9 primarily degrades collagen type IV, the main component of the basement membrane .…”
Section: Discussionmentioning
confidence: 99%